Early learning curve changes in objective performance indicators during robotic cholecystectomy - Liu, Derrick; Shields, Mallory; Stricklin, Catherine; Troxler, Casey; Jarc, Anthony; Feinn, Richard; Soto, Leland (Frontiers in Surgery, 2025)
Learning curves for experienced laparoscopic surgeons transitioning to the robotic platform are still unknown. With the new availability of objective performance indicators (OPIs), which provide information on surgical behavior, we identified when a surgeon becomes proficient in transitioning from laparoscopic to robotic technique. As more operations were performed, the time all four robotic arms moved decreased for cystic duct ligation/division (p = 0.042), master clutch use increased for cystic artery ligation/division (p = 0.009), and camera velocity, acceleration, and smoothness increased for multiple steps. CUSUM analysis generated a learning curve for idle time, with proficiency attained after 22 operations. As the first study to evaluate objective metrics throughout a learning curve for newly performing robotic cholecystectomy, we identify relevant OPIs that may be critical for future proficiency tracking, 8 of which impact a surgical step with a steep learning curve in transitioning from laparoscopic to robotic cholecystectomy, cystic duct ligation/division.